Evaluation and Comparison of Fracture Strength and Fluoride Releasing Properties of New Alkasite Materials with Conventional Restorative Material, Bulk Fill Composite and Glass Ionomer Cement: An In-Vitro Study - Savan K. Kashiyani; Shreya A. Khanna; Leena Jobanputra; Niharika Patel; Hirenkumar P. Patel; Apoorva D. Patel (Journal of Pharmacy and Bioallied Sciences)
Aim: This study aimed to evaluate and compare fluoride ion release by Cention-N (self-cure and light-cure) and conventional glass-ionomer cement (GIC) at different pH levels and time intervals. Methodology: For fluoride release assessment, 240 samples (10 mm diameter, 2 mm height) of Cention-N and conventional glass-ionomer cement were created using rubber rings. Samples were stored in deionized water, and the cumulative fluoride ion release and change in pH were assessed using a spectrophotometer and pH meter, respectively, at the end of 7 days, 14 days, and 21 days. The obtained data were subjected to statistical analysis. Results: All three samples exhibited very high fluoride release in an acidic medium compared to the neutral medium. Although GIC demonstrated superior fluoride release, Cention-N displayed adequate fluoride release over a longer duration. Conclusions: Within the limitations of this study, it can be concluded that both Glass ionomer cement and Cention-N showed an initial fluoride burst.